2013
DOI: 10.1103/physrevb.88.014201
|View full text |Cite
|
Sign up to set email alerts
|

Topological insulator in the presence of spatially correlated disorder

Abstract: We investigate the effect of spatially correlated disorder on two-dimensional topological insulators and on the quantum spin Hall effect which the helical edge states in these systems give rise to. Our work expands the scope of previous investigations which found that uncorrelated disorder can induce a nontrivial phase called the topological Anderson insulator (TAI). In extension of these studies, we find that spatial correlations in the disorder can entirely suppress the emergence of the TAI phase. We show th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 57 publications
2
34
0
Order By: Relevance
“…Moreover, it was found that the bulk states can be effectively localized by the long-range disorder, but the edge states are much more robust [199]. Furthermore, in contrast to the Anderson disorder without spatial correlation, the finite correlation length disorder was found to be detrimental to (or even totally suppress) the formation of the topological Anderson insulator [204]. The presence of several types of disorder, Rashba spin-orbit coupling, the finite-size effect [205] as well as correlation make it challenging to observe topological Anderson insulator.…”
Section: H Topological Anderson Insulatormentioning
confidence: 99%
“…Moreover, it was found that the bulk states can be effectively localized by the long-range disorder, but the edge states are much more robust [199]. Furthermore, in contrast to the Anderson disorder without spatial correlation, the finite correlation length disorder was found to be detrimental to (or even totally suppress) the formation of the topological Anderson insulator [204]. The presence of several types of disorder, Rashba spin-orbit coupling, the finite-size effect [205] as well as correlation make it challenging to observe topological Anderson insulator.…”
Section: H Topological Anderson Insulatormentioning
confidence: 99%
“…On the other hand, it also been realized that disorder itself can cause an ordinary insulator to undergo a phase transition to a topological insulator (topological Anderson insulator) [21][22][23][24]. In turn, such a transition may be strongly modified when disorder exhibits spatial correlations [25].…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32] It is indicated that TAI is dependent on the type of disorder, for example, TAI phase is absent for the magnetic disorder and spatially correlated disorder. 33,34 On the other hand, gapped and gapless topological phases and transport characteristics in layered structures and thin films have been studied recently in the presence and absence of disorder. [35][36][37] It is interesting to note that Kobayashi et al revealed the TAI phase in topological insulator nanofilms by numerical calculations.…”
Section: Introductionmentioning
confidence: 99%